Review and Prospect of “Micro-Credit” Courses in Higher Education SPROUT Project (HESP) - Liza Lee; Yi-Yi Liu (International Journal of Social Sciences and Artistic Innovations)
We delved into the challenges encountered during the implementation of micro-credit courses, specifically “Application of the Multiple Intelligences Theory in Designing Teaching Aids” and “Children's Poetry and Song Creation” in 2020. The objective of this study was a meticulous analysis of course effectiveness, focusing on student satisfaction and feedback. In the “Application of the Multiple Intelligences Theory in Designing Teaching Aids” course, 42% of the 50 students rated satisfaction at 5, 44% at 4, and 14% at 3. In the “Children’s Poetry and Song Creation” course, 53% of the 48 students rated satisfaction at 5, 33% at 4, and 14% at 3. Feedback from the students who attended “Application of the Multiple Intelligences Theory in Designing Teaching Aids” highlighted satisfaction with the course content and the instructor’s conscientiousness. However, several students suggested reducing the volume of teaching aids. For “Children’s Poetry and Song Creation”, students acknowledged the instructor’s diligence but recommended more emphasis on “teaching aid creation. Challenges included a disparity between student preferences and departmental focus, non-cross-disciplinary course restrictions, limited promotion leading to a narrow student pool, budget constraints affecting instructional materials, and short, sporadic course durations hindering effective assessment.